2008
DOI: 10.1002/pros.20791
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic inflammation and obstructive voiding in the adult noble rat: Impact of the testosterone to estradiol ratio in serum

Abstract: Different responses of the prostatic inflammation and voiding function to the change in T-to-E(2) ratio imply that non-bacterial prostatic inflammation is not a sufficient condition for the development of obstructive voiding. The present study finds no support for the idea that age- and/or obesity-related hypoandrogenic state with a decreased ratio of T-to-E(2) would cause urethral obstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 33 publications
2
47
0
Order By: Relevance
“…Investigations on animals confirm that changes in the physiological ratio of both hormones contribute to a gradual increase in the prostate volume and disturbances in urination [23]. Nevertheless, the study of Bernoulli et al [23] fails to confirm the hypothesis that a decrease in the ratio of testosterone to estradiol is associated with LUTS. However, Tao et al [24] found that patients with BPH had higher estradiol levels than patients without BPH.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on animals confirm that changes in the physiological ratio of both hormones contribute to a gradual increase in the prostate volume and disturbances in urination [23]. Nevertheless, the study of Bernoulli et al [23] fails to confirm the hypothesis that a decrease in the ratio of testosterone to estradiol is associated with LUTS. However, Tao et al [24] found that patients with BPH had higher estradiol levels than patients without BPH.…”
Section: Discussionmentioning
confidence: 99%
“…17 Bernoulli et al showed that the reduction of the serum TT:E2 ratio is associated with onset of non-bacterial prostatitis without urodynamic alterations in the animal model with hypoandrogenism combined with hyperestrogenism, while obstructive disorders appeared in the hyperandrogenic animals with low serum TT:E2 ratio. 18 In another experimental model, chronic treatment with estrogens results in the activation of metalloproteinases 2,7,9 in the lateral lobe of the prostate and increase of leukocyte infiltrate. 19 Other conceivable causes could be represented by the functional alterations of aromatase, the enzyme responsible for the conversion of T into E2, which are more frequent in infertile patients, 20 or the TT reduction associated with the psychological stress which is another important characteristic of patients with chronic prostate inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in a rat study with E2 treatment plus different doses of T, obstructive voiding was only observed in treated rats with hyperandrogenic state but not in those with hypoandrogenic state. 32 The 12.1DMT1 mice carry a genomic alteration targeted at an intergenic region adjacent to Grin2a. The genomic modification includes an insertion of a transgene cassette expressing MT1 under probasin promoter and a concomitant deletion of a B12.1-kb genomic region.…”
Section: Wtmentioning
confidence: 99%